Perceptions of dental students’ regarding anatomy learning and assessment in integrated curriculum adopted by Shaheed Zulfiqar Ali Bhutto Medical University, Pakistan - Muazam, Shazia; Anbreen Aziz; Maryam Shan; Shazia Imran; Hina Kundi; Resham Hafeez (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: The integrated curriculum adopted by the university affects the learning process of dental students. They prefer selective study of specific objectives rather than developing a deeper understanding of anatomy. Thus, students’ perceptions would be helpful in improving curriculum delivery, at university level, for beneficial future clinical roles. METHODOLOGY: A qualitative exploratory study in a dental college affiliated with regional medical university spread over three months. Second year BDS class (50 students) was purposively chosen excluding first year students. Fifteen item questionnaire was developed and distributed via Google form followed by inductive analysis. RESULTS: Forty-eight students (96%) responded. Seven themes and eighteen subthemes emerged. Three themes expressed students’ preference for group study, small group discussion and visual learning style. Content of anatomy was suggested to be divided in two years by few. In theme “Anatomy assessment weightage” majority consented on same number of multiple-choice questions of anatomy as other subjects as all found it difficult to prepare it in one day with other subjects. Most of them considered such anatomy assessment weightage to have a positive impact on their future practitioner role. CONCLUSION: Dental students are satisfied with the content of anatomy in each block. Main concern raised is misalignment between anatomy assessment weightage and its delivered content. This drives students to do selective anatomy study in each block. This concern should be considered by university in redesigning future curriculum to equip students with necessary knowledge of anatomy required by dentists in their future roles.